A Survey of the Knowledge, Attitudes and Practices of a Sample of Albanian Medical Students in Relation to Occupational Exposure to Biological Agents - Lorenzo Ippoliti; Luca Coppeta; Ersilia Buonomo; Giuseppina Somma; Giuseppe Bizzarro; Cristiana Ferrari; Andrea Mazza; Agostino Paolino; Claudia Salvi; Vittorio Caputi; Antonio Pietroiusti; Andrea Magrini (Diseases)
(1) Background: Exposure to blood carries the risk of transmission of many infectious diseases. Healthcare workers (HCWs), including hospital-based medical students, face high and often under-reported rates of exposure to needlestick and sharps injuries. Previous studies have shown that students’ knowledge of infection control varies, highlighting the importance of pre-placement training. This study aims to assess knowledge, attitudes and practices regarding these risks in a population of medical students from Albania. (2) Methods: A validated questionnaire was administered to 134 medical students in an Italian hospital in May 2023. It assessed HBV vaccination status, adherence to infection control practices, knowledge of pathogen transmission, exposure incidents and attitudes towards infected patients. Three additional questions addressed air-borne transmission of tuberculosis and vaccination recommendations for healthcare workers. (3) Results: Most students (64%) reported being aware of occupational exposure risks. While 93% and 87%, respectively, recognised HIV and HBV as blood-borne pathogens, fewer recognised Treponema pallidum (44%). Awareness of post-exposure prophylaxis for HIV was high (85%), but although 75% reported having received training, only 45% felt it was adequate. Statistical analysis revealed an association between knowledge of infection control, awareness of pathogen transmission and understanding of the importance of vaccination. (4) Conclusions: Our study highlights gaps in medical students’ knowledge of occupational infections and highlights the need for improved pre-clerkship education. Improved education could reduce anxiety, ethical issues and misconceptions and promote safer healthcare practices.